Characteristics of refugee women's access to health services during pregnancy and puerperium: an integrative review (Research, Society and Development, 2022)
Objective: To characterize the access to health services of refugee women in their pregnancy-puerperal cycle in the global context. Methods: Integrative literature review whose searches were performed in PUBMED, LILACS and CINAHL databases. Studies published from 1996 to 2021 were observed. Results: Sixteen studies were selected for the final sample, according to the previously established criteria. Two themes were highlighted: Characteristics of access to health services by refugee women in the pregnancy-puerperal period and strategies used to promote better access to health. The analysis and synthesis of the results revealed the following characteristics: language barriers, late search for care, difficulties in obtaining health insurance, higher incidence of complications in pregnancy and puerperium, higher incidence of depression, problems with means of transportation, stigma and cultural discrimination, legal difficulties related to immigration, among others, as well as successful strategies and specific recommendations. Conclusion: By characterizing access, the study revealed barriers encountered by refugees in obtaining access to health care. Thus, it is essential to establish public policies worldwide that can provide adequate access to health care during pregnancy and puerperium to this vulnerable population.